An analysis of the systemic risks posed by Fannie Mae and Freddie Mac and an evaluation of the policy options for reducing those risks - Robert A. Eisenbeis; W. Scott Frame; Larry D. Wall (Federal Reserve Bank of Atlanta, 2006)
Fannie Mae and Freddie Mac are government-sponsored enterprises that are central players in U.S. secondary mortgage markets. Over the past decade, these institutions have amassed enormous mortgage- and non-mortgage-oriented investment portfolios that pose significant interest-rate risks to the companies and a systemic risk to the financial system. This paper describes the nature of these risks and systemic concerns and then evaluates several policy options for reducing the institutions' investment portfolios. We conclude that limits on portfolio size (assets or liabilities) would be the most desirable approach to mitigating the systemic risk posed by Fannie Mae and Freddie Mac.
Keywords: 330; Hypothek; Öffentliches Unternehmen; Hypothekenbank; USA